Identity representations through Machinima Creation - Theodore Thomas; Marina Vihou (5th Global Conference on Cybercultures, with Digital Memories: Exploring Critical Issues, 2010)
his paper investigates identity representations through a narrative perspective. It examines the reproduction of social stereotypes through the creation of machinima films created by the students of the Department of French language at the University of Athens. According to Giddens΄s project of social and self identity and Ricoeur’s interpretation theories, the machinima films will be considered as an eloquent reflection of their creators’ representations. They claim that narrative is the dialectical process, between me and the other, through which the person is constantly led to a conscious identity adjustment. Based on this assumption, we investigate the mediating role of machinima, animated filmmaking within a real-time virtual 3-D environment, in the identity awareness of the subject. We study the representations produced by a group of students through the evaluation of the signifying practice of the creation of machinima films they have created during a Cyberculture course